Christianity in China, Tartary and Thibet - Huc, Evariste Régis (D. & J. Sadlier, 1857)
v. 1. From the apostleship of St. Thomas to the discovery of the Cape of Good Hope -- v. 2. From the discovery of the Cape of Good Hope to the establishment of the Mantchoo-Tartar dynasty in China.